The Development and Decay of the Working Alliance During Time-limited Counselling - Horvath, Adam O.; Marx, Ronald W. (Canadian Journal of Counselling and Psychotherapy, 2011)
Time limited ( 10 sessions) counselling treatments were examined to explore the history of the working alliance over time. Similar patterns of working alliance development were reported by the two counsellors across the four clients. The initial development phase of the working relationship appears to be followed by a period when the relationship decays. There were indications that the working alliances were repaired during the final sessions.